Principles of corporate finance - Brealey, Richard A.; Allen, Franklin , 1956-; Myers, Stewart C. (The McGraw-Hill/Irwin series in finance, insurance, and real estate, 2011)
Shows how managers use financial theory to solve practical problems. This title includes chapters that cover the time value of money, the valuation of bonds and stocks, and practical capital budgeting decisions. It also discusses market efficiency, payout policy, and capital structure, option valuation, and financial planning and analysis